Chrześcijaństwo pozakonfesjonalne i Søren Kierkegaard - TOEPLITZ, KAROL (Filozofia Chrześcijańska, 2018)
According to Søren Kierkegaard, the development of Christianity is a history of going away from it, or at least of mitigating the criteria of belonging to it. Dane proposes two models of the trans confessional faith: (1) The recognition of the earthly life of Jesus Christ, of his death and resurrection, and nothing more. (2) The recognition of the faith as that which was defi ned above in the fi rst point and, additionally, on this basis of the choice of the Bible, which is possible as the secondary act related to the faith but not as its starting point. Moreover, all the interpretations of the beyond-confessional faith should be subjectively considered by a single individual. Kierkegaard mentions here some mystical elements. All the religious relationships should be personal in character. As far as the questions of faith and reason are concerned, the standpoint of Paulinism – either/or – is binding. Kierkegaard demands that the existing churches recognise themselves as representing the mitigated forms of Christianity; otherwise they have to undergo criticism. For him, the fi rst two centuries of the existence of Christianity are the ideal ones, and the personal model is the „witness of the truth”, of which he gives the detailed description. The increasing phenomenon of the trans-confessional faith has its roots in the civilisational changes (the secularization) as well as in the intensive manifestation, in the history of Christianity, of the practices which are inconsistent with the biblical background.